The Effect of Temperature on Extraction of Swietenia Mahagoni by Ultrasound–assisted Extraction (UAE) Method - Ike Dayi Febriana; Heri Septya Kusuma; Selfina Galan; Mahfud Mahfud (Department of Chemical Engineering, Universitas Gadjah Mada, 2016)
Azo dyes are synthetic organic dyes which have azo group (-N=N-) as chromophore. Waste of azo dyes have not been able to overcome completely so that requires solutions of natural dye. Raw material of natural dye can be obtained from Swietenia mahagoni. Natural dye can be extracted by ultrasound-assisted extraction (UAE) method. The pupose of this research is to study the factor that influence UAE. Observed factor is influence of extraction temperature to the yield of natural dye. This research was conducted using ratio of material to solvent of 0.05 g/L with extraction time at 40 minute. Extraction temperature was observed at 30, 40, and 50oC. Ultrasonic wave that used for this research at 40 kHz. The result is increasing temperature will be allow the increasing trend of yield. The result indicate that there is about 9.2748% improvement in the yield of extract due to increasing extraction temperature from 30oC to 50oC